Single-petal rosette trajectory for 2D functional lung imaging - Frantz, Hanna; Speidel, Tobias; Rasche, Volker (Frontiers in Physics, 2024)
Purpose To investigate the use of a 2D rosette trajectory for breath-hold and free-breathing real-time imaging of the lung.Methods Eight healthy volunteers underwent breath-hold MRI using two different parametrizations of the proposed single-petal rosette trajectory (SPR), as well as radial UTE acquisition combined with the tiny golden angle acquisition scheme. Additional free-breathing acquisitions of all trajectories were performed. The proposed technique was compared with the conventional radial UTE technique regarding image sharpness, signal-to-noise ratio (SNR), regional fractional ventilation (FV) for breath-hold and retrospective image-based self-gating, and real-time imaging capabilities.Image sharpness significantly increased for gated SPR images compared to radial UTE for the end-expriatory stage, no significant difference was found for the self-gated end-inspiratory stage and the breath-hold acquisitions. The SPR trajectory performs significantly better to radial UTE concerning SNR for breath-hold imaging, whereas no significant difference was found for self-gated images. Fractional ventilation values were comparable between SPR and radial UTE. SPR real-time data showed a markedly reduction in aliasing artifacts with no apparent streaks.The second half of the petal of the SPR trajectory accomplishes rephasing while acquiring non-redundant k-space data, thus leading to more efficient sampling of k-space compared to the radial UTE sampling scheme with minimal increase in TR. This leads to the need of less read-outs to achieve the same SNR values and thus a reduction in scan time. For real-time application, the SPR approach resulted in a markedly reduction of aliasing artifacts when compared to UTE.